2021
DOI: 10.3389/fpls.2021.709197
|View full text |Cite
|
Sign up to set email alerts
|

Integration of miRNAs, Degradome, and Transcriptome Omics Uncovers a Complex Regulatory Network and Provides Insights Into Lipid and Fatty Acid Synthesis During Sesame Seed Development

Abstract: Sesame (Sesamum indicum L.) has always been known as a health-promoting oilseed crop because of its nutrient-rich oil. In recent years, studies have focused on lipid and fatty acid (FA) biosynthesis in various plants by high-throughput sequencing. Here, we integrated transcriptomics, small RNAs, and the degradome to establish a comprehensive reserve intensive on key regulatory micro RNA (miRNA)-targeting circuits to better understand the transcriptional and translational regulation of the oil biosynthesis mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…SAD desaturates stearoyl-ACP (18:0) to form oleic acid (18:1), and FAD2 catalyzes synthesis of linoleic acid (18:2) from oleic acid (18:1) [ 24 ]. The expression pattern of SAD and FAD2 corresponds with oleic acid (18:1) and linoleic acid (18:2) at the early and middle stages of developing seeds of sesame [ 126 ]. The oleosins have been linked to lipids’ biosynthesis/metabolism and the size of seed oil bodies [ 127 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAD desaturates stearoyl-ACP (18:0) to form oleic acid (18:1), and FAD2 catalyzes synthesis of linoleic acid (18:2) from oleic acid (18:1) [ 24 ]. The expression pattern of SAD and FAD2 corresponds with oleic acid (18:1) and linoleic acid (18:2) at the early and middle stages of developing seeds of sesame [ 126 ]. The oleosins have been linked to lipids’ biosynthesis/metabolism and the size of seed oil bodies [ 127 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…For in silico expression analysis of sesame seed development, RNA-seq data of variety S. indicum var. ‘Wanzhi No.2’ during seed development comprising 7 days after flowering (7 DAF, S1), 14 DAF (S2), 21 DAF (S3) and full maturity (28 DAF, S4) were used (PRJNA739094) ( Zhang et al., 2021 ). For in silico expression analysis, the RNA-seq data of the disease-resistant variety S. indicum var.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [ 77 ] identified 351 known miRNAs and 91 novel miRNAs from 18 sesame libraries, and 116 miRNAs were found to be involved in the salt-stress response through the comparison between the salt-treated group and the control group. Subsequently, Zhang et al [ 92 ] sequenced a total of 220 miRNAs in seed development and constructed a regulatory co-expression network through transcriptomics, small RNAs and degradome. The FAD2, LOC10515945, LOC105161564, and LOC105162196 genes were observed for regulating the accumulation of unsaturated fatty acid biosynthesis.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…In terms of organ development, seeds, leaves, carpels, roots, fertile and sterile buds are introduced [ 41 , 55 , 86 , 87 , 88 , 89 , 90 ]. It also introduces several non-coding RNAs, such as tRNAs, rRNAs, miRNAs, lncRNAs [ 77 , 91 , 92 , 93 ].…”
Section: Figurementioning
confidence: 99%